Peran Mediasi Sebagai Bentuk Diversi Dalam Alternatif Penyelesaian SengketaTindak Pidana Anak di Bawah Umur (Studi Kasus di Polres Kota Bengkulu) - Baihaqi Mumtazy; Muhammad Reyhan Saputra; Muhammad Rofiq; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The purpose of this study is to analyze the role of mediation as a form of diversion in Alternative Dispute Resolution (ADR) for juvenile crimes at the Bengkulu City Police Resort, focusing on its position as a non-litigation mechanism recognized by positive law. This study uses a normative approach with a literature review method. The results of the study indicate that mediation as a form of diversion is the simplest and most flexible form of Alternative Dispute Resolution (ADR), as it allows the parties to communicate directly with the involvement of a third party as a mediator. Mediation not only produces a mutually beneficial solution (win-win solution) but also maintains good relations between the disputing parties, unlike litigation processes that tend to produce winners and losers. Furthermore, the results of mediation can be legally binding if outlined in a peace agreement and ratified by the court, thus having the same legal force as a court decision. Thus, mediation as a form of diversion plays a strategic role in resolving disputes involving juvenile crimes peacefully and efficiently while maintaining long-term relationships between the parties